Discourses of the Alberta Oil Sands: What Key Stakeholders Really Think About Sustainability - Sutton, Matt (Consilience, 2017)
In an attempt to determine the key challenges and opportunities of creating a dialogue about sustainability in regards to the Alberta oil sands, 13 professionals from four key stakeholder groups (industry, government, media and NGO) were asked the same set of seven questions about their conceptualization of sustainability. Key findings included the following: (1) Vague language pervaded many of the discussions including references to ‘responsible development,’ ‘corporate social responsibility,’ or ‘triple bottom line.’ (2) The sample illustrated a continuum of positions regarding both the notion of sustainability writ large and within the context of the oil sands specifically. (3) The largest concentration of discussion about sustainability surrounded practices and values, with goals and indicators figuring much less prominently. This paper provides useful insight to both the areas where stakeholders are still struggling to agree upon and those places where there is in fact some overlap. Areas for future research include exploration into one more key stakeholder: the indigenous voice.